Systemic evaluation of cutaneous sarcoidosis: 15‐year dermatology experience at University Hospital Limerick. (6th March 2022) - Byrne, Berbie; Goh, Alicia; Izham, Nor Fatin; Porter, Emma; Field, Sinéad
Summary: Sarcoidosis is a multisystem granulomatous disease that can affect almost any organ including the skin, liver, ocular, cardiac, renal, nervous, musculoskeletal and endocrine systems. Systemic evaluation is indicated in all patients diagnosed with cutaneous sarcoidosis, as it is associated with asymptomatic systemic disease in 30%–40% of patients. Guidelines recommend that patients diagnosed with sarcoidosis undergo baseline and surveillance investigations including full blood count (FBC), renal and liver profile, Vitamin D, serum calcium, electrocardiography (ECG), chest radiography, pulmonary function tests (PFTs) and ophthalmology examination to assess for systemic involvement. Recommendations for surveillance monitoring vary on interval duration but include regular FBC, biochemistry, chest radiography and PFTs, with additional investigations and prompt referral to respective specialties as indicated.. We conducted a retrospective analysis to evaluate extracutaneous involvement and systemic evaluation of patients diagnosed with cutaneous sarcoidosis during the period 2004–2020, and compared our findings with international guidelines. Cutaneous manifestation was the primary presentation for 67% of the patients (12 of 18), an extracutaneous disease subsequently developed in 67% (8 of 12) of these patients. Baseline investigations included chest radiography (94%; 17 of 18), PFTs (39%; 7 of 18), FBC (94% (17 of 18), renal profile (89%; 16 of 18), liver function tests (83%; 15 of 18) and serum calcium (89%; 16 of 18); ECG was performed for 4 (25%) of 16 patients. No Vitamin D levels were recorded. Specialist referral was required for 89% (16 of 18); of these 16 patients, 94% (15 of 16) required referral to the Respiratory Medicine department, 69% (11 of 16) to Ophthalmology and 19% (3 of 16) to Nephrology. The results highlight the importance of a structured protocol for the systemic evaluation of patients diagnosed with cutaneous sarcoidosis. We subsequently developed a baseline and surveillance protocol for the assessment of extracutaneous disease in patients at University Hospital Limerick. Abstract : Systemic evaluation is indicated in all patients with cutaneous sarcoidosis, as it is associated with asymptomatic systemic disease in 30%–40% of patients. A retrospective analysis was conducted to evaluate extracutaneous involvement and systemic evaluation of patients diagnosed with cutaneous sarcoidosis during 2004–2020. Of the 18 patients included, cutaneous manifestation was the primary presentation for 12 and extracutaneous disease subsequently developed in 8 of these; therefore, for 14 of the 18 patients, cutaneous sarcoidosis was associated with extracutaneous manifestations. Specialist referral was required for 16 patients. The results highlight the importance of the structured protocol subsequently developed at University Hospital Limerick for systemic evaluation of patients with cutaneous sarcoidosis.